(3GdeMUhd aj CUhd Gdabgs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s; (3CHj YHO Gddg aNQ GdOjf eMeO Hf YeQ Hf GdMSjfj GdQGRj, GHf GdNWjH,J (B606 (3g` s ((3MdH (B_ (3eOQSI GdSdWGf edc GdXGgQ s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg agPg GddZI hGYJQGVi GdCMOGK YdjgG hcKQI JZJQgG hGdLhGH GddZI hGdfMh Ydi bSejf CMOgeG GdeJOGhd GdeTghQ hGdYde GdVQhQi s
(3BNQgG (B:s
(3hGYde CfG EfeG LeYfG gPg GdhLhg dCf GcKQ efGXQ Cf Cgd GdReGf ai Gdabg OGFQI Ydi CeKGd gPg GdcdeGJ Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1615s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs